2012
DOI: 10.4161/auto.19716
|View full text |Cite
|
Sign up to set email alerts
|

ER stress inhibits neuronal death by promoting autophagy

Abstract: These authors contributed equally to this work.Keywords: ER stress, autophagy, Parkinson, apoptosis, Drosophila, mouse Endoplasmic reticulum (ER) stress has been implicated in neurodegenerative diseases but its relationship and role in disease progression remain unclear. Using genetic and pharmacological approaches, we showed that mild ER stress ("preconditioning") is neuroprotective in Drosophila and mouse models of Parkinson disease. In addition, we found that the combination of mild ER stress and apoptotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(152 citation statements)
references
References 57 publications
9
138
1
Order By: Relevance
“…In mammalian cells, ER stress preconditioning protects against brain ischemia and attenuates heart ischemia/reperfusion (22,23). More recent findings support the direct involvement of a hormesis mechanism in handling neuronal degeneration through preconditioning mediated by a dynamic balance between ER stress and autophagy (21). In C. elegans, the notion of hormesis has been previously related to the effect of oxidative stress on longevity and dauer diapause (31)(32)(33), and mildly elevated temperature on heat-induced necrosis (34).…”
Section: Hormesis Contributes To Er Stress Resistance In the Absence mentioning
confidence: 80%
See 1 more Smart Citation
“…In mammalian cells, ER stress preconditioning protects against brain ischemia and attenuates heart ischemia/reperfusion (22,23). More recent findings support the direct involvement of a hormesis mechanism in handling neuronal degeneration through preconditioning mediated by a dynamic balance between ER stress and autophagy (21). In C. elegans, the notion of hormesis has been previously related to the effect of oxidative stress on longevity and dauer diapause (31)(32)(33), and mildly elevated temperature on heat-induced necrosis (34).…”
Section: Hormesis Contributes To Er Stress Resistance In the Absence mentioning
confidence: 80%
“…ER hormesis has previously been described in Drosophila and mammalian cell systems (21)(22)(23). To test whether this mechanism is conserved in C. elegans, we first exposed wild-type animals to low doses of TM, which on their own have no effect on viability, followed by higher doses normally associated with decreased survival.…”
Section: Hpl-2 Plays Opposing Functions In the Intestine And Neuronalmentioning
confidence: 99%
“…However, eIF2α phosphorylation is also an indicator of ER unfolded protein response (UPR ER ). Indeed, BiP/GRP78, the master regulator of UPR ER transduction pathway, [44][45][46] was upregulated in dYME1L del flies throughout their adulthood (Supplementary Figure S5a). In addition, the general cellular protein turnover mechanisms, autophagy and ubiquitin-proteasome system, were both activated in the mutant flies (Figures 6c and d).…”
Section: Resultsmentioning
confidence: 99%
“…autophagy may also mediate the benefits of preconditioning in Drosophila and mouse Parkinson's disease models (Fouillet et al 2012;Matus et al 2012). In these studies, inhibition of autophagy was found to impair endoplasmic reticulum stress-induced protection.…”
Section: Adaptation and Sensitization To Proteotoxic Stressmentioning
confidence: 99%